Formulation and Evaluation of the Antibacterial Activity of Paper Soap Containing Acalypha wilkesiana Muell. Arg. Leaf Extract Against Escherichia coli - Rike Septianingrum; Lina Winarti; Nafisah Isnawati (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2026)
Background: One of the effective ways to maintain a healthy body is to maintain hand hygiene. Keeping your hands clean can be done by washing your hands with soap. One of the development of soap products is paper soap using the active ingredient of akalifa leaf plant extract (Acalypha wilkesiana Muell. Arg) which contains secondary metabolites including flavonoids, tanins, saponins, and alkaloids. Purpose: The purpose of this study is to formulate paper soap of akalifa leaves (Acalypha wilkesiana Muell. Arg) with an extract concentration of 5%, 7%, 9% and tested antibacterial activity on Escherichia coli. Methods: This research method is laboratory experiment by formulating evaluation and testing of antibacterial activity of paper soap preparations. Results:  The results of the research on phytochemical screening of akalifa leaf extract positively contain tanin compounds, flavonoids, saponins, and alkaloids. Paper soap formulations made with variations of 5% (F1), 7% (F2), and 9% (F3) akalifa leaf extract. It shows pH values of 8.34 ± 0.15 (F1), 9.04 ± 0.11 (F2), and 9.01 ± 0.09 (F3) so that it meets the requirements of SNI (pH 4-10). Testing the height of the foam with values of 73.0 mm ± 0.26 (F1), 76.3 mm ± 0.15 (F2), and 78.6 mm ± 0.20 (F3) so that it meets the requirements of SNI 13-220 mm. The test of washing time with values of 18.35 seconds ± 0.16 (F1), 19.08 seconds ± 0.18 (F2), and 18.99 seconds ± 0.14 (F3) met the criteria, namely (15-292 seconds). The moisture content test with values of 0.24% ± 0.05 (F1), 0.09% ± 0.03 (F2), and 0.18% ± 0.02 (F3) met the criteria because (<15%). The results of the antibacterial activity test of akalifa leaf extract paper soap had antibacterial activity against Escherichia coli with F1 having an inhibition zone of 4.15 mm ± 0.87, F2 6.39 mm ± 1.22, F3 8.79 mm ± 1.25, positive control 18.31 mm ± 2.24, and negative control 0 mm. Conclusions: The conclusion of this study is that akalifa leaf extract is positive for containing secondary metabolite compounds, namely alkaloids, flavonoids, tannins, and saponins. Evaluation of the physical quality of paper soap obtained results that met the requirements in accordance with Indonesia's National Standards. In the results of antibacterial activity, there is an increased.